2014
DOI: 10.1016/j.jphotobiol.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Stable synthetic mono-substituted cationic bacteriochlorins mediate selective broad-spectrum photoinactivation of drug-resistant pathogens at nanomolar concentrations

Abstract: A set of three stable synthetic mono-substituted cationic bacteriochlorins (BC37, BC38 and BC39) were recently reported to show exceptional activity (low nanomolar) in mediating photodynamic killing of human cancer cells after a 24 h incubation upon excitation with near-infrared light (730 nm). The presence of cationic quaternary ammonium groups in each compound suggested likely activity as antimicrobial photosensitizers. Herein this hypothesis was tested against a panel of pathogenic microorganisms that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…The new bacteriochlorin derivative known as LUZ11 [27] recently entered clinical trials for head and neck cancer in Portugal (Photodynamic Therapy With LUZ11 in Advanced Head and Neck Cancer, Clinical Trials.Gov NCT02070432). Other bacteriochlorin structures have been tested as PSs for both anti-cancer [28] and antimicrobial applications [29]. Near-infrared light between 700 and 800 nm is used to activate bacteriochlorins and this was shown to be particularly effective against pigmented tumours such as malignant melanoma [30].…”
Section: Tetrapyrrole Structuresmentioning
confidence: 99%
“…The new bacteriochlorin derivative known as LUZ11 [27] recently entered clinical trials for head and neck cancer in Portugal (Photodynamic Therapy With LUZ11 in Advanced Head and Neck Cancer, Clinical Trials.Gov NCT02070432). Other bacteriochlorin structures have been tested as PSs for both anti-cancer [28] and antimicrobial applications [29]. Near-infrared light between 700 and 800 nm is used to activate bacteriochlorins and this was shown to be particularly effective against pigmented tumours such as malignant melanoma [30].…”
Section: Tetrapyrrole Structuresmentioning
confidence: 99%
“…The only remaining requirement is to have quaternary cationic groups present on the BC to allow binding and penetration of the bacterial cells [27]. Interestingly we found that an asymmetric dicationic BC was actually significantly more active against Gram-positive bacteria and fungi than a symmetrically substituted tetracationic BC (that only had high activity against Gram-negatives) presumably due to the molecular asymmetry allowing better penetration into the bacterial cell [28] (see Figure 4). This difference was particularly pronounced with eukaryotic fungal cells.…”
Section: New Photosensitizersmentioning
confidence: 99%
“…Both types of ROS photoproduction processes occur simultaneously, but it has been suggested that Type II mechanism is mainly responsible for bacteria death [304,319]. Even though the antimicrobial mode of action is not yet fully understood, and PDI is not yet an established therapeutic procedure, the efficacy of PDI to eradicate a variety of resistant bacteria strains and the diversity of applications demonstrated in recent years, show that PDI is a promising method for disinfection and/or sterilization.…”
Section: Photodynamic Inactivation Of Microorganisms (Pdi)mentioning
confidence: 99%